Vietnamese immigration in Poland: issues of education and integration for children - Nguyen DuyKhang; Phan Thi Tuyet Van (Problemy Wczesnej Edukacji)
This paper investigates the issues of education and integration conditions for Vietnamese immigrants’ children in Poland. These points of interest were primarily treated as the additional research connected with our teaching practices. It was conducted as an empirical study with three non-standardised interviews with the families, informal observations, and group discussions. Regardless of the limitation of a perhaps not significantly substantial range of data, the study led to the outlining of some concerns connected with the process of education and integration of the children in these Vietnamese families. The main four findings which are related to the research question are: the cultural differences and expectations of the parents, the language barriers of the parents, the typical stereotypes of educating children at home, and the conflicts of self-identification in the future. The research implied that children from all the immigrant groups should be assessed as to their growth as well as to the quality of their adaptation into the society.